Oral Administration of 17α-Methyltestosterone Increased Male Percentage of Freshwater Crayfish Cherax quadricarinatus - O. Carman; M.Y. Jamal; . Alimuddin (Jurnal Akuakultur Indonesia)
Cherax quadricarinatus is one of freshwater crayfish species that has enormous potential for expanding its farming in future.  Application of monosex male culture using steroid sex hormone administration method during the period of sex differentiation or early developmental stage might be increased efficiency in farming.  This study was aimed to increase male of C. quadricarinatus by oral administration of diet containing 17α-methyltestosterone (MT) towards production efficiency.  Two-week-old of Cherax quadricarinatus were fed ad libitum on diets containing various dose of MT, i.e., 25, 50, 75, 100 and 150 mg/kg diet or diet containing no MT as control, 3 times daily for 30 days.  After MT-treatment, crayfish were fed frozen Chironomus sp.  and shrimp diet.  Sex ratio, survival and growth rate (by length and weight) were observed at the end of experiment.  Sex was determined by visual observation; the male sex organ is located at the fifth walking leg while the female is at the third.  Data was analyzed by F and BNT tests.  The results of study show that administration of MT was significantly changed the male ratio of crayfish.  Treatment dose of 50 mg/kg diet was effective to increase male sex percentage from 24.93% (control) to be 59.96%. Growth was also significantly being improved, while survival rate was insignificant.  Thus, oral administration of MT is an effective way to increase male sex percentage of crayfish, although other methods and the time of hormone administration are needed to be verified to obtain maximal results.